Penerapan Metode Analytical Hierarchy Process(AHP) dan Promethee II dalam Rekomendasi Kelayakan Calon Pengurus Himpunan Mahasiswa Jurusan - Syafrida, Desy; Zufria, Ilka (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Student organizations are an interpretation of organizations that accommodate students in carrying out and developing their roles. The benefits of organizations for students include as a forum for honing soft skills, fostering a sense of concern for the social environment, and increasing student selling points as provisions to support the future. One of the student organizations at the university is the Department of Student Association. The problem that often occurs in major student associations is selecting potential new members who determine the success of the association in the future. So a decision is needed in selecting the existing criteria as the best prospective member who will be selected as a new member or who has high loyalty to the student association of one's own department. However, during the selection process for selecting the best member candidates, the department's student association experienced difficulties because there were so many candidates to be selected. The author conducted research and combined two methods, namely Analytical Hierarchy Process (AHP) and Promethee II. This merger aims to overcome the problem of determining the criteria for the best administrator candidates in the UINSU Computer Science Department Student Association. Next, the author will build a decision support application that makes it easier to process data, compare criteria, and produce the best alternative. Overcoming the problem of criteria for being the best candidate for major student association administrators, namely by combining the Analytical Hierarchy Process (AHP) method in collaboration with the Promethee II method. To test the criteria and eligibility for prospective administrators of the UINSU computer science student association. Design and build applications that can support decisions with several conflicting criteria and alternatives that will produce the greatest value which will later be selected as the best alternative. Decision support system and makes it easy to select recommendations for the suitability of candidates for departmental student association management. The selection results are obtained from the alternative results with the highest final value. The system that has been built can be used by UINSU, so that UINSU can select prospective association administrators as departmental student association administrators.